2021
DOI: 10.21203/rs.3.rs-252260/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Herpes Zoster Infection in Patients With Chronic Kidney Disease: A Case-control Study

Abstract: Background: Chronic kidney disease (CKD) increases the susceptibility to the infection of herpes zoster (HZ). Less is known about the risk factors of HZ in CKD patients.Methods and Participants: This is a case-control study. CKD patients diagnosed with HZ infection between January 2015 and October 2020 in a tertiary hospital were identified. One age- and gender- matched control was paired for each case, matched to the date of initial HZ diagnose. The uni- and multivariate analysis were used to evaluate the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Perforating CD was not an independent risk factor for the development of postoperative intestinal fistula. Wang et al [15] included 142 Chinese patients with CD and suggested that patients with perforating CD are more likely to develop recurrence after surgery. Perforation lesions in the intestinal wall can involve adjacent organs and tissues, forming enterovesical or rectovaginal fistulas and leading to abdominal abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…Perforating CD was not an independent risk factor for the development of postoperative intestinal fistula. Wang et al [15] included 142 Chinese patients with CD and suggested that patients with perforating CD are more likely to develop recurrence after surgery. Perforation lesions in the intestinal wall can involve adjacent organs and tissues, forming enterovesical or rectovaginal fistulas and leading to abdominal abscesses.…”
Section: Discussionmentioning
confidence: 99%